Glacier Mass Balance Changes Over the Turgen Daban Range, Western Qilian Shan, From 1966/75 to 2020 - Xu, Song; Wang, Yetang; Wang, Yuzhe; Qi, Shanzhong; Zhou, Min (Frontiers in Earth Science, 2022)
Extensive efforts for quantifying regional glacier mass balance in the Qilian Mountains have been made using the geodetic method, but these estimations were rarely extended back to the period before 2000. This study presents glacier mass budgets in the Turgen Daban Range, over the Western Qilian Mountain, from 1966/75 to 2020 by means of the digital elevation models (DEMs) generated by the topographic maps and ASTER images. The results show that the glacier mass decreased by -18.79 ± 12.48 m w.e. during the past 50 years. The average mass loss rate is estimated to be -0.19 ± 0.08 m w.e.a-1 for the 1966/75-2006 period, and -0.45 ± 0.17 m w.e.a-1 during 2006–2020, respectively, suggesting a remarkable acceleration of glacier mass loss. This may be attributable to the significant increase in air temperature, and the insignificant precipitation increase which cannot offset glacier melting caused by increased temperature. Due to the melting and shrinking of glaciers, the area of glacial lakes increases by 2.83 km2 from 1987 to 2020.